2011
DOI: 10.1111/j.1467-9248.2011.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Governing Health Risk by Buying Behaviour

Abstract: This paper considers the role of conditional cash transfers as a mechanism of governing health risk by buying behaviour change in sexual practice. Conditional cash transfers have come to be identified as a potential solution to the problem of HIV prevention, and as such look likely to be applied throughout countries with high prevalence rates in sub-Saharan Africa. The paper considers the implications of two pilot studies in Tanzania and Malawi for governing the risk of HIV infection. It outlines the problem o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The international response to the security threat posed by HIV/AIDS had already foreshadowed this tendency. In the case of the AIDS pandemic anti-retroviral drug programmes were in many cases initiated in the armed forces, and later rolled out more generally to civilian populations in Africa through quite unprecedented initiatives like the US President's Emergency Plan for AIDS Relief (PEPFAR) and the Global Fund to Fight AIDS, Tuberculosis and Malaria (Harman, 2011, this issue). In many Western countries that medical response model was subsequently also adopted in the development of domestic pandemic preparedness more generally.…”
Section: Magic Bullets: Stockpiling Medical Countermeasuresmentioning
confidence: 99%
“…The international response to the security threat posed by HIV/AIDS had already foreshadowed this tendency. In the case of the AIDS pandemic anti-retroviral drug programmes were in many cases initiated in the armed forces, and later rolled out more generally to civilian populations in Africa through quite unprecedented initiatives like the US President's Emergency Plan for AIDS Relief (PEPFAR) and the Global Fund to Fight AIDS, Tuberculosis and Malaria (Harman, 2011, this issue). In many Western countries that medical response model was subsequently also adopted in the development of domestic pandemic preparedness more generally.…”
Section: Magic Bullets: Stockpiling Medical Countermeasuresmentioning
confidence: 99%
“…Literature has shown that HIV/AIDS affects people in their productive age groups (15 -49 years), resulting in a loss of agricultural labour [8][9][10][11]. In addition caregivers who have to give up working in the fields and farms in order to take care of the sick who will be deprived of labour for agricultural activities [12,13].…”
Section: Introductionmentioning
confidence: 99%